Co-composting of chitinous materials and oil palm wastes to improve quality of empty fruit bunch (EFB) compost as an organic fertilizer - Lai, Jia Chi (Curtin University, 2014)
Raw shrimp shells are selected as an alternate nitrogen supplement to improve the quality of empty fruit bunch (EFB) compost as an organic fertilizer. The composting of EFB and raw shrimp shells with POME was performed in laboratory scale at three different temperatures. Better characteristics and quality of EFB compost was obtained at 40°C. An empirical model was developed to represent relationship between nitrogen content of EFB compost and respective process variables